Developmental coordination disorder and internalizing problems in children: The environmental stress hypothesis elaborated - Cairney, J.; Rigoli, Daniela; Piek, Jan Patricia (Academic Press, 2013)
There is a growing literature connecting poor motor coordination to physical and mental health outcomes in children and adolescents. These studies suggest that children with disorders such as developmental coordination disorder (DCD) are at greater risk for depression and anxiety, as well as obesity, and poor physical fitness. With regard to internalizing problems (symptoms of depression and anxiety), there is also evidence to suggest that the environment may play an important role in the etiology of psychological distress in this population. Cairney, Veldhuizen & Szatmari (2010) used the phrase “environmental stress hypothesis” to highlight the role that negative exposure to personal and interpersonal stressors might play in accounting for higher rates of internalizing symptoms in children with DCD. In this paper, we elaborate further on this basic premise, offering a model linking DCD to internalizing problems based on Pearlin’s stress process framework. In addition to stressors (risk) and protective factors, we incorporate both physical activity and obesity into our stress model. Next, we review the existing literature to see if there is evidence supporting specific components (pathways) of the model. In doing so, areas in need of further research are identified. Implications for intervention are also provided.